2022
DOI: 10.3390/microorganisms10061084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pathogenic Potential of Escherichia coli Strains Isolated from Eye Infections

Abstract: While primarily Gram-positive bacteria cause bacterial eye infections, several Gram-negative species also pose eye health risks. Currently, few studies have tried to understand the pathogenic mechanisms involved in E. coli eye infections. Therefore, this study aimed to establish the pathogenic potential of E. coli strains isolated from eye infections. Twenty-two strains isolated between 2005 and 2019 from patients with keratitis or conjunctivitis were included and submitted to traditional polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…The type-3 secretion system (T3SS) is a highly conserved virulence factor in disease-causing Gram-negative bacteria and is responsible for injecting bacterial effector proteins directly into the host cell cytoplasm [ 79 ]. Similarly, iron acquisition genes sitABCD mediate manganese–iron transfer and are essential for bacterial survival in iron-deficient environments [ 80 ]. The gene hlyA was also encoded in the UM869 genome, which is homologous to the α-hemolysin gene of E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…The type-3 secretion system (T3SS) is a highly conserved virulence factor in disease-causing Gram-negative bacteria and is responsible for injecting bacterial effector proteins directly into the host cell cytoplasm [ 79 ]. Similarly, iron acquisition genes sitABCD mediate manganese–iron transfer and are essential for bacterial survival in iron-deficient environments [ 80 ]. The gene hlyA was also encoded in the UM869 genome, which is homologous to the α-hemolysin gene of E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli , which causes most UTIs and RUTIs ( 3 , 8 ), is a diverse species that can be divided into phylogenetic groups ( 9 , 10 ). Although strains from several phylogenetic groups are pathogenic ( 11 , 12 ), group B2 strains are more prevalent in UTIs and RUTIs ( 8 , 11 , 12 ), as well as in E. coli -caused neonatal meningitis ( 13 , 14 ), inflammatory bowel diseases (Crohn’s disease and ulcerative colitis) ( 15 17 ), and eye infections ( 18 ), are more often associated with colorectal cancer ( 19 ), and have more characteristics associated with multiple antibiotic resistance and extended spectrum β-lactamase production ( 20 ). Paradoxically, a phylogenetic evolutionary analysis found that group B2 strains have lost several environmental-adaptive genes, including genes for survival in extreme conditions of low pH, high temperature, and low osmolarity ( 21 ).…”
Section: Introductionmentioning
confidence: 99%